Answer:
Rational
Step-by-step explanationRational interger:
40% of 20 is 8 Boys
60% of 20 is 12 Girls
50% of the Girls is 6
25% of the Boys is 2
6 + 2 = 8 Students wore glasses
Hope this helps!
This pattern of question is always coming up. Since we can't easily guess, then let us set up simultaneous equation for the statements.
let the two numbers be x and y.
Multiply to 44. x*y = 44 ..........(a)
Add up to 12. x + y = 12 .........(b)
From (b)
y = 12 - x .......(c)
Substitute (c) into (a)
x*y = 44
x*(12 - x) = 44
12x - x² = 44
-x² + 12x = 44
-x² + 12x - 44 = 0.
Multiply both sides by -1
-1(-x² + 12x - 44) = -1*0
x² - 12x + 44 = 0.
This does not look factorizable, so let us just use quadratic formula
comparing to ax² + bx + c = 0, x² - 12x + 44 = 0, a = 1, b = -12, c = 44
x = (-b + √(b² - 4ac)) /2a or (-b - √(b² - 4ac)) /2a
x = (-(-12) + √((-12)² - 4*1*44) )/ (2*1)
x = (12 + √(144 - 176) )/ 2
x = (12 + √-32 )/ 2
√-32 = √(-1 *32) = √-1 * √32 = i * √(16 *2) = i*√16 *√2 = i*4*√2 = 4i√2
Where i is a complex number. Note the equation has two values. We shall include the second, that has negative sign before the square root.
x = (12 + √-32 )/ 2 or (12 - √-32 )/ 2
x = (12 + 4i√2 )/ 2 (12 - 4i√2 )/ 2
x = 12/2 + (4i√2)/2 12/2 - (4i√2)/2
x = 6 + 2i√2 or 6 - 2i√2
Recall equation (c):
y = 12 - x, When x = 6 + 2i√2, y = 12 - (6 + 2i√2) = 12 - 6 - 2i√2 = 6 - 2i√2
When x = 6 - 2i√2, y = 12 - (6 - 2i√2) = 12 - 6 + 2i√2 = 6 + 2i√2
x = 6 + 2i√2, y = 6 - 2i√2
x = 6 - 2i√2, y = 6 + 2i√2
Therefore the two numbers that multiply to 44 and add up to 12 are:
6 + 2i√2 and 6 - 2i√2
Answer: First Option
a) exponential function going through point (0, 2) and ending up on the right
Step-by-step explanation:
Look at the attached image, the red line represents a function of the form:
![f(x) = 2^x](https://tex.z-dn.net/?f=f%28x%29%20%3D%202%5Ex)
Note that this function cuts to the axis and at the point (0, 1)
Also when x tends to ∞ f(x) tends to ∞ and when f(x) tends to -∞ then f(x) tends to zero.
If we perform the transformation
then the graph of y is equal to the graph of f(x) displaced 1 unit up. Then the new cutting point with the axis y will be: (0, 2) as shown in the attached image (blue line)
The transform function is ![y =2^x +1](https://tex.z-dn.net/?f=y%20%3D2%5Ex%20%2B1)
Finally the answer is the first option